The behavior of the company in the conditions of monopoly. Antitrust policy of the state. - NIKOLAEVICH, BOROBOV VASILY; MIKHAILOVICH, BODNARUK NIKOLAY; MIKHAILOVNA, BUDANOVA IRINA; VALERIEVICH, GOLOVIN VLADIMIR (The journal of contemporary issues in business and government, 2021)
The scientific article reveals the essence of monopoly, its types, the behavior of the company in the conditions of monopoly. The role of the state in regulating the activities of monopolies is considered. A set of measures on antimonopoly policy is proposed.